Religijne oblicze komunizmu - Tyszka, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
The article is devoted to the issue of the presence of religious motives both in communist ideology and in the practice of political systems defined as such. This matter is a part of a much wider problem which was analyzed by many scholars since the October Revolution. What is communism? Is it a strictly political project which has the ambition to holistically transform the social reality? Or does it – precisely because of its radicalism and holistic ambitions – extend beyond a realm of ordinary political projects? Communism is a type of social utopia branded with many themes specific for religious thinking. The article invokes the texts of many authors who, in various historical periods and from different ideological perspectives, attempted to indicate and demonstrate the roots and manifestations of religious motives in communism. Starting with Bierdiajew’s philosophy, through Kołakowski’s, Aron’s and Furet’s analyzes, to sovietologist studies of Bocheński and Besancon, there remains a common conviction that communism was shaped as a direct consequence of the Enlightenment philosophy and of the social projects which were inspired by it the idea of social progress. Although each of the above-mentioned authors sees the course and manifestations of this process a bit differently, they all share identical general conclusion: the assessment of communism as a scientifically proven stage of historical process made this idea a very negation of science, a quasi-religious system of beliefs, defined by Besancon as ideology. One of the features of communism is a sui generis vision of the world and a peculiar language used to describe it.
Keywords: religia; komunizm; ideologia